Line positions and intensities of the ν4 band of methyl iodide using mid-infrared optical frequency comb Fourier transform spectroscopy. (November 2020) - Sadiek, Ibrahim; Hjältén, Adrian; Senna Vieira, Francisco; Lu, Chuang; Stuhr, Michael; Foltynowicz, Aleksandra
Highlights: High-resolution spectra of CH3 I are measured in the CH stretch region from 2800 to 3160 cm -1 using a mid-infrared comb-based Fourier transform spectrometer with comb-mode limited resolution. New improved assignment is presented for the ν4 band and the nearby ν3 +ν4 -ν3 hot band. 2603 transitions are assigned to the ν4 band with standard deviation (observed – calculated) of 0.00034 cm -1, and 831 transitions are assigned to the ν3 +ν4 -ν3 hot band with standard deviation of 0.00084 cm -1 . Hyperfine splittings due to the 127 I nuclear quadrupole moment are observed for transitions with J ≤ 2 × K in the ν4 band. Line intensities are reported for 157 isolated transitions in the ν4 band. Abstract: We use optical frequency comb Fourier transform spectroscopy to measure high-resolution spectra of iodomethane, CH3 I, in the CH stretch region from 2800 to 3160 cm -1 . The fast-scanning Fourier transform spectrometer with auto-balanced detection is based on a difference frequency generation comb with repetition rate, f rep, of 125 MHz. A series of spectra with sample point spacing equal to f rep are measured at different f rep settings and interleaved to yield sampling point spacing of 11 MHz. Iodomethane is introduced into a 76 m long multipass absorption cell by its vapor pressure at room temperature. The measured spectrum contains three main ro-vibrational features: the parallel vibrational overtone and combination bands centered around 2850 cm -1, the symmetric stretch ν1 band centered at 2971 cm -1, and the asymmetric stretch ν4 band centered at 3060 cm -1 . The spectra of the ν4 band and the nearby ν3 +ν4 -ν3 hot band are simulated using PGOPHER and a new assignment of these bands is presented. The resolved ro-vibrational structures are used in a least square fit together with the microwave data to provide the upper state parameters. We assign 2603 transitions to the ν4 band with a standard deviation (observed – calculated) of 0.00034 cm -1, and 831 transitions to the ν3 +ν4 -ν3 hot band with a standard deviation of 0.00084 cm -1 . For comparison, in the earlier work using standard FT-IR with 162 MHz resolution [Anttila, et al., J. Mol. Spectrosc. 1986; 119:190–200] 1830 transition were assigned to the ν4 band, and 380 transitions to the ν3 +ν4 -ν3 hot band, with standard deviations of 0.00083 cm -1 and 0.0013 cm -1, respectively. The hyperfine splittings due to the 127 I nuclear quadrupole moment are observed for transitions with J ≤ 2 × K . Finally, intensities of 157 isolated transitions in the ν4 band are reported for the first time using the Voigt line shape as a model in multispectral fitting.